Managements and Tourists Knowledge and Appreciation of Eco-Labeling and Eco-Certification at Selected Coastal Tourist Destinations in Lagos, Nigeria - F, Ajani; B.T, Omobuwa; O.O, Ajayi (Journal of Tourism Management Research, 2019)
Eco-labels and eco-certification are environmental tools that help tourism providers to adopt environmentally sustainable practices. Although widely adopted in developed countries, there is little information available in developing countries. This study therefore assessed both management’s and tourists’ knowledge and appreciation of eco-labeling and eco-certification at Santa Cruz and Suntan Beach Resorts in Lagos State, Nigeria. Key informant interviews were conducted with the managers of both sites to determine their level of knowledge about the concept and the type of eco-label awarded. A total of 372 structured questionnaires totaling 372 were administered, proportionately, among tourists at both sites, based on convenience sampling. The data collected was statistically analyzed using descriptive statistics, the t-test, and Pearson product–moment correlation. The results revealed that the Director of Santa Cruz Beach did know about eco-labels and eco-certification, but not the Manager of Suntan Beach; however, neither beach resort have completed eco-certification and acquired an eco-label. With respect to tourists, no significant difference between Santa Cruz and Suntan Beaches exists (p>0.05) in either their knowledge and appreciation of the value of eco-labels (p > 0.05) or their interest in and response to eco-labeled products (p > 0.05). Tourists at Santa Cruz Beach, however, have a more favorable response (56.7%) to eco-labeled products than at Suntan Beach (48.5%). Finally, a positive correlation (p < 0.05) exists between tourists’ knowledge of and responsiveness to eco-labels and eco-certification. This study thus concludes that the eco-labels and eco-certification for tourist destinations should be promoted in the Nigerian tourism sector.